Rhodanine derived enethiols react to give 1,3-dithiolanes and mixed disulfides † - Kamps, JJAG; Zhang, D; Claridge, TDW; Schofield, CJ (Royal Society of Chemistry, 2024)
Rhodanines have been characterised as ‘difficult to progress’ compounds for medicinal use, though one rhodanine is used for diabetes mellitus treatment and others are in clinical development. Rhodanines can undergo hydrolysis to enethiols which are inhibitors of metallo-enzymes, such as metallo β-lactamases. We report that in DMSO, rhodanine derived enethiols undergo dimerisations to give 1,3-dithiolanes and mixed disulfides. The results highlight the potential of rhodanines and enethiols to give multiple products. They suggest that where possible DMSO should be avoided as a storage solvent for rhodanines/enethiols and highlight the need for further research on biologically relevant enethiols/mixed disulfides.